TIME DEPENDENT RELIABILITY ASSESSMENT OF MALAYSIA’S JACKET PLATFORM - AZHAR, MOHAMAD HAIQAL (IRC, 2016)
The offshore jacket platform is certainly facing the harsh environment in the sea. Typically, the resistance of the jacket platform is assumed to be constant throughout its design life. However, the exposure of jacket platform to the sea environment and occurrence of corrosion will definitely reduce the resistance of the platform. The situation could lead to the failure of the jacket platform as the environmental load will be continuously acting on the structure. Hence, the time dependent reliability method is extremely needed to assess the reliability of the jacket platform in different reference time. By performing time dependent reliability method, the probability of failure of the jacket platform in different reference time is expected as the outcome of this study. The time dependent reliability analysis is conducted based on limit state function. In order to satisfy the limit state function, the variables such as resistance and load are scrutinized. In this study, platform A located near shore of Bintulu, Sarawak is selected.